Sistem Informasi Usulan Dan Rekapitulasi Usulan Anggaran Serta Laporan Realisasi Dana Desa (Sireda) Berbasis Web Responsive Pada Desa Mekar Bhuwana, Kecamatan Abiansemal, Kabupaten Badung - I Gusti Made Adi Putra; I Putu Satwika; Ketut Queena Fredlina (Primakara University, 2020)
Village Funds (DD) are funds sourced from the State Revenue and Expenditure Budget which is intended for the Village. Transferred through the Regency / City Regional Revenue and Expenditure Budget, which is used to finance governance, development, community development and community empowerment. The budget allocation for village funds is a serious concern because the funds obtained by each village are quite large, which is almost one billion rupiah. These funds must always be reported to the community so that there is no decrease in community trust in the village apparatus. Village funds with a large enough nominal are vulnerable to abuse by village officials who do not have a nationalist and irresponsible sense. The Mekar Bhuwana Village Office still uses conventional methods in the budgeting process to the reporting of the village budget, so that many of the archive proposals are lost because they are still in the form of hardcopy. Therefore we need a system that can handle the process of submitting village funds and the realization of village funds that have been submitted. This system was developed with the waterfall method where data is obtained directly from Mekar Bhuwana Village, system analysis and design using Data Flow Diagrams and Entity Relationship Diagrams with system creation software using PHP programming language with laravel framework and MySQL database. The results of the research are that the system can work well to handle the process of proposing and realizing village funds.